The use of desmopressin (DDAVP) for nocturia in women with multiple sclerosis. Issue 9 (September 1983) - Hilton, P; Hertogs, K; Stanton, S L
Abstract : Sixteen women with multiple sclerosis who complained of nocturia completed a double-blind cross-over trial of Desmopressin (DDAVP) and placebo. Nocturia was reduced from a mean of 2.55 voids to 2.01 with placebo and to 1.28 with Desmopressin (p less than 0.01, for the difference between placebo and Desmopressin). Side effects were minor, and equally distributed between treatment and placebo.